To forage, mate, or thermoregulate: Influence of resource manipulation on male rattlesnake behavior. Issue 16 (20th July 2017) - Tetzlaff, Sasha J.; Carter, Evin T.; DeGregorio, Brett A.; Ravesi, Michael J.; Kingsbury, Bruce A.
Abstract: Male animals should preferentially allocate their time to performing activities that promote enhancing reproductive opportunity, but the need to acquire resources for growth and survival may compete with those behaviors in the short term. Thus, behaviors which require differing movement patterns such as ambushing prey and actively searching for mates can be mutually exclusive. Consequently, males that succeed at foraging could invest greater time and energy into mate searching. We radio‐tracked sixteen male massasauga rattlesnakes ( Sistrurus catenatus ) and supplemented the diets of half the snakes with mice across an active season. We tested the predictions that reduced foraging needs would allow fed snakes to move (i.e., mate search) more, but that they would consequently be stationary to thermoregulate less, than unfed controls. Contrary to our first prediction, we found no evidence that fed snakes altered their mate searching behavior compared to controls. However, we found controls maintained higher body temperatures than fed snakes during the breeding season, perhaps because fed snakes spent less time in exposed ambush sites. Fed snakes had higher body condition scores than controls when the breeding season ended. Our results suggest the potential costs incurred by devoting time to stationary foraging may be outweighed by the drive to increase mating opportunities. Such instances may be especially valuable for massasaugas and other temperate reptiles that can remain inactive for upwards of half their lives or longer in some cases, and for female rattlesnakes that generally exhibit biennial or more protracted reproductive cycles. Abstract : Behaviors which require differing movement patterns such as ambushing prey and actively searching for mates could be mutually exclusive. Mate searching movements of male rattlesnakes with reduced foraging needs from supplemental food did not differ from naturally foraging males, but supplemented snakes were in better body condition at the conclusion of the breeding season. The potential costs incurred by allocating time to stationary foraging may be outweighed by the drive to increase mating opportunities, particularly for species with low energy demands.